Jalan jihad sang dokter - Joserizal Jurnalis; Rita Budiarti (Jakarta : Qanita, 2011)
Author's account on medical care as a volunteer doctor.
Text in indonesian.
Keywords: Volunteer workers in medical care -- Gaza; Medical assistance -- Gaza; Humanitarian assistance -- Gaza